2002
DOI: 10.1128/aem.68.12.5911-5917.2002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter jejuni , Campylobacter lari , and Campylobacter coli in Different Ecological Guilds and Taxa of Migrating Birds

Abstract: A total of 1,794 migrating birds trapped at a coastal site in southern Sweden were sampled for detection of Campylobacter spp. All isolates phenotypically identified as Campylobacter jejuni and a subset of those identified as non-C. jejuni were identified to the species level by PCR-based techniques. C. jejuni was found in 5.0% of the birds, Campylobacter lari was found in 5.6%, and Campylobacter coli was found in 0.9%. An additional 10.7% of the tested birds were infected with hippurate hydrolysis-negative Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
245
5
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(278 citation statements)
references
References 32 publications
(31 reference statements)
17
245
5
3
Order By: Relevance
“…Therefore, the natural environment is an important reservoir of the UPTC organisms. However, in a study by Waldenstrom et al [184] were unable to detect any UPTC organisms in a wild bird population in Sweden.…”
Section: Atypical Campylobactersmentioning
confidence: 90%
“…Therefore, the natural environment is an important reservoir of the UPTC organisms. However, in a study by Waldenstrom et al [184] were unable to detect any UPTC organisms in a wild bird population in Sweden.…”
Section: Atypical Campylobactersmentioning
confidence: 90%
“…Waldenstrom et al (2002) monitored various wild birds and found that the mean prevalence of Campylobacter spp. infection was 21.6% for all tested birds, but differed significantly between ecological guilds of birds and seems to be linked to various phylogenetic factors.…”
Section: Resultsmentioning
confidence: 99%
“…is frequently found in feces of healthy animals, especially birds and is widely distributed in the environment (Engvall et al, 2002;Workman et al, 2005). Wild birds are often considered to be a potential reservoir for C. jejuni in nature and possible source of human infections (Levesque et al, 2000;Waldenstrom et al, 2002). So far, however, genotyping methods were rarely used to examine whether bacterial isolates found in wild birds are comparable with those isolated from humans with clinical disease.…”
mentioning
confidence: 99%
“…We now recognize that avian migration can be an efficient mode of transport for avian microorganisms [16,33] and a catalyst for infection by endoparasites and pathogens [12]. Furthermore, with the emergence of highly pathogenic diseases such as avian influenza [16] and West Nile virus [20], avian migration has become a topic of multidisciplinary concern (e.g., [13,26]).…”
Section: Introductionmentioning
confidence: 99%
“…Burtt and Ichida [5], Lucas et al [18], and Peele et al [22] showed that feather-degrading bacilli and plumage microbial communities varied geographically and locally among habitats. Although focusing on fecal microbes, Waldenström et al [33] found that Campylobacter spp. were more common in short-distance than long-distance migratory birds.…”
Section: Introductionmentioning
confidence: 99%